Ontology-based Chatbot to Support Monitoring of Server Performance and Security By Rule-base - Fauzan Ishlakhuddin; Azhari SN (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
The server is a computer program or a device that provides functionality for other programs or devices, called